PENGENDALIAN INTERN PEMERINTAH DAN AKUNTABILITAS PUBLIK TERHADAP KINERJA INSTANSI PEMERINTAH DI KOTA BENGKULU ( Studi Pada OPD Kota Bengkulu ) - Nur Cholis; Fadli Fadli (UNIB Press, 2018)
This research is a quantitative research that aims to see whether there is influence of information technology utilization, internal control system of government and public accountability to performance of government institution. This study uses the Organization of Regional Devices (OPD) Bengkulu City as a sample of research. The sample selection in this research is done by using purposive sampling method. Hypothesis testing in this study used Multiple Linear Regression Analysis with the help of SPSS program and 5% significance level (0,05). The result of the test is 1) there is significant influence of the utilization of information technology to the performance of government institution, 2) there is significant influence of internal control system of government performance of government institution, 3) there is significant influence of public accountability to performance of government institution.Key Words: Technology, System, Accountability, Government